‘A teacher is no politician’: stereotypic attitudes of secondary school teachers in Kenya - Kuppens, Line; Langer, Arnim; Ibrahim, Sulley (International journal of educational development, 2018)
More than affecting their academic performance, teachers’ stereotypic attitudes may impact society at large by shaping pupils’ inter-group attitudes. Whereas particularly teachers in post-conflict and divided societies may have negative inter-group attitudes, extremely little research has been conducted in these contexts. Based on a large-scale survey of secondary school teachers (N=925) and 68 in-depth follow-up interviews in Nairobi, this paper aims to address this void by examining teachers’ inter-group attitudes in Kenya, an ethnically divided society. While their attitudes appear to be stereotype-congruent, we find that Kenyan teachers seem careful of not letting their own stereotypes influence their teaching practices.